2018
DOI: 10.1002/ccd.27789
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long‐term outcomes after polytetrafluoroethylene or pericardium covered stenting for grade 3 coronary artery perforations: Insights from G3‐CAP registry

Abstract: Background: Covered stent (CS) implantation is considered a useful device in the setting of Grade III Coronary Perforation (G3CP), one of the most harmful PCI complication. However, data regarding efficacy of this device and clinical outcomes are still limited. Methods and results: From 1993 to 2015, among 97,779 patients from 9 European centres undergoing PCI, 224 patients had G3CP (0.23%), and 102 patients were managed with CS implantation (96 with PTFE, 6 with pericardium). Device oriented composite endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…during short-and long-term follow-up (> 12 months), our results implicate that better outcomes (TLF rate < 5%) might be achieved after implantation of CS devices by applying the presented hybrid approach [3,6,7,[22][23][24].…”
Section: Discussionmentioning
confidence: 89%
“…during short-and long-term follow-up (> 12 months), our results implicate that better outcomes (TLF rate < 5%) might be achieved after implantation of CS devices by applying the presented hybrid approach [3,6,7,[22][23][24].…”
Section: Discussionmentioning
confidence: 89%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect the combination of population with high burden of cardiovascular risk factors and complex lesions. Reported rates of in-hospital mortality for PTFE-CS in studies involving more patients ranged from 15% to 23% [ 20 , 26 ] and those of PU-CS were approximately 10% [ 19 , 21 ]. At 1-year follow-up, figures of all-cause mortality for PTFE-CS ranged from 26% to 41% [ 16 , 20 ], and those of PU-CS were approximately 26% [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Nagaraja and colleagues, the long-term mortality for patients receiving Graftmaster, PK Papyrus, and pericardial stents after CAP was 18.5%, 16.0%, and 26.1%, respectively [ 23 ]. Pavani et al conducted an investigation of 102 patients treated with CS (96 with PTFE-CS and 6 with pericardium-CS) after a dreadful grade III CAP and reported that the in-hospital MACE were mainly caused by high in-hospital mortality (14.7%) and acute ST (3.9%) whereas the long-term follow-up was acceptable despite a high ST (6.2%) [ 26 ]. And the cardiac tamponade was the critical sign of poor prognosis especially referring to the mortality rate at short-term follow-up [ 16 ].…”
Section: Discussionmentioning
confidence: 99%